Upaya Meningkatkan Kebutuhan Aktivitas Dan Latihan Pada Ibu Post Partum - Febriani, Tyas; , Dr. Faizah Betty Rahayuningsih, A., S.Kep., M.Kes; , Winarsih Nur Ambarwati S.Kep. Ns.ETN. M.Kep (2017)
Introduction. Normal labor is a birth of baby with mothers own energy without tools help and does not harm the mother and baby. Postpartum mothers are potentially vulnerable to postnatal care complications such as, fatigue and exhaustion, anorexia, insomnia, incontinence, constipation, postpartum blues and depression. It is appropriate to improve the physical, mental and social prosperity. Postpartum mothers with first child often complain about perineum pain and afraid to move. The purpose of this study is to fulfill the activity and exercise on postpartum mothers. Author conducted the study in February. The method used by the author is observation, interview and documentation. The result of research by the author obtained physical mobility hindrance caused by pain. Intervention by the author includes pain observation, breathing relaxation training, early ambulation training. After conducting nursing intervention for three days, the activity and exercise can be fulfilled, so the intervention stopped.